2013
DOI: 10.1021/ja406077j
|View full text |Cite
|
Sign up to set email alerts
|

A “Turn-On” Fluorescent Sensor for Methylglyoxal

Abstract: Methylglyoxal (MGO), a dicarbonyl metabolite produced by all living cells, has been associated with a number of human diseases. However, studies of the role(s) MGO plays biologically have been handicapped by a lack of direct methods for its monitoring and detection. To address this limitation, we have developed a fluorescent sensor (methyl diaminobenzene-BODIPY, or "MBo") that can detect MGO under physiological conditions. We show that MBo is selective for MGO over other biologically relevant dicarbonyls and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 41 publications
4
124
0
4
Order By: Relevance
“…The response is potentiated markedly by addition of exogenous MG. Similar findings were reported with the BODIPY-related probe by Wang et al [27]. DAF-2DA was also used to assess whether increased fluorescence could be detected in cells using a microplate based-cell assay with A549 cells cultured in 96-well plates.…”
Section: Detection Of Dicarbonyls In Live Cells In Vitrosupporting
confidence: 68%
See 3 more Smart Citations
“…The response is potentiated markedly by addition of exogenous MG. Similar findings were reported with the BODIPY-related probe by Wang et al [27]. DAF-2DA was also used to assess whether increased fluorescence could be detected in cells using a microplate based-cell assay with A549 cells cultured in 96-well plates.…”
Section: Detection Of Dicarbonyls In Live Cells In Vitrosupporting
confidence: 68%
“…We have shown in our studies that MG reacts with DAF-2 and DAR-1 to produce a characteristic fluorophore and, moreover, the development of related increased fluorescence can be used to report on MG and other dicarbonyl concentrations. Wang et al [27] recently synthesized MBo (methyl -1 studies). a.u., arbitrary units.…”
Section: Comparison Of Daf-2 Dar-1 and Bodipy-derived Fluorogenic Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the large number of chromogenic receptors for the sensing of metal ions, [11][12][13] very few chromogenic receptors for anions and small molecules have been developed that are based on recognition approaches. [13][14][15][16] In fact, a thorough literature survey revealed that there are very few colorimetric or fluorogenic sensors which dealt with the use of synthetically constructed receptors in carboxylic acids sensing purpose. [17][18] Supramolecular concepts [19][20] in designing new optical chemosensors has become a very common trend in recent-past based on changes in fluorescence [21][22][23] and in absorbance [24][25][26] as the output signals.…”
mentioning
confidence: 99%